La apropiacion politica del territorio. Estrategias de participacion política y de resistencia campesina en los Llanos del Yarí (2014)
This current article shows the results of an investigation that dealt with the scenarios of political participation in the Yari Plains, a region inhabited by peasants from Communist tradition, with the historic presence of the FARC and where the State deploys the largest counterinsurgency strategy which has been moved forward in the history of the country since 2003. To such effect, our focus of attention is directed to the existing relationship between the conditions of the political exercise (understood as the construction of the sense of the political and the definition or participation in political scenarios per se) with the history of the process of territorial appropriation. Such inspection has enabled us to establish that in this region, the platform of action of the community organization, is both its political and social platform, as its political-electoral scenario. We will delve deeply into these relationships from the narratives of peasant experiences, the social conditions in the region, and the acute war situation that people experience there